The Thought of KH Ahmad Sanusi (1889-1950) in Da’wah and Education Paradigm - Shodiqin, Asep (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
KH Ahmad Sanusi adalah sosok yang memiliki karakter pemikiran yang unik. Dalam beberapa hal ia memiliki pemikiran yang berbeda dalam memandang praktek keagamaan, khususnya dalam koteks hegemoni pemikiran modernis maupun tradisionalis. Keterlibatan KH Ahmad Sanusi dalam perdebatan-perdebatan yang bersifat furu’iyyah baik dengan kalangan modern maupun dengan kalangan tradisional merupakan suatu bukti bahwa ia merupakan tokoh yang berpengaruh secara intelektual dalam persoalan agama. Permasalahan pokok yang dikaji dalam tulisan ini adalah karakter pemikiran keagamaan KH Ahmad Sanusi yang mengambil posisi tidak menerima sepenuhnya terhadap kalangan tradisionalis dan tidak pula berpihak secara sepenuhnya pada pandangan-pandangan kaum modernis, terutama fokusnya pada pemikiran dakwah dan pendidikan.Kata kunci: Da’wah, Pendidikan, Tafsir. KH Ahmad Sanusi is a figure who has a unique character of thought. In some ways he has different ideas in view of religious practice, especially in the hegemony of modernist and traditionalist hegemony. KH Ahmad Sanusi's involvement in furu'iyyah debates both with the modern and the traditional is a proof that he is an intellectually influential figure in religious matters. The main issue examined in this paper is the character of KH Ahmad Sanusi's religious thought which takes a position of not fully accepting the traditionalists and is not entirely aligned with the views of the modernists, especially its focus on da'wah and education. Keyword : Da’wah, Education, Tafseer